Structured Organic–Inorganic Perovskite toward a Distributed Feedback Laser. Issue 5 (2nd December 2015) - Saliba, Michael; Wood, Simon M.; Patel, Jay B.; Nayak, Pabitra K.; Huang, Jian; Alexander‐Webber, Jack A.; Wenger, Bernard; Stranks, Samuel D.; Hörantner, Maximilian T.; Wang, Jacob Tse‐Wei; Nicholas, Robin J.; Herz, Laura M.; et al.
Abstract : A general strategy for the in‐plane structuring of organic–inorganic perovskite films is presented. The method is used to fabricate an industrially relevant distributed feedback (DFB) cavity, which is a critical step toward all‐electrially pumped injection laser diodes. This approach opens the prospects of perovskite materials for much improved optical control in LEDs, solar cells, and also toward applications as optical devices.